2003
DOI: 10.1038/sj.npp.1300016
|View full text |Cite
|
Sign up to set email alerts
|

Flattening the Corticosterone Rhythm Attenuates 5-HT1A Autoreceptor Function in the Rat: Relevance for Depression

Abstract: Depression is associated with glucocorticoid abnormalities, in particular a flattening of the diurnal cortisol rhythm. Recent data suggest that an important factor in the aetiology of depression may be a deficit in the function and expression of 5-HT 1A receptors, which has been reported in depressed patients. The present study assessed the possibility that this cortisol abnormality is causal in the 5-HT 1A receptor deficits. First, a rat model of flattened glucocorticoid rhythm was developed. Controlled relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
59
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 48 publications
4
59
0
2
Order By: Relevance
“…This is manifest in a flattening of the normal diurnal rhythm of glucocorticoid levels together with an elevation of nadir levels (Deuschle et al, 1997;Wong et al, 2000). We have recently shown in rats, that flattening the glucocorticoid rhythm, with an elevation of the nadir, causes a desensitization of somatodendritic 5-HT 1A autoreceptors (Leitch et al, 2003). Hence the response of 5-HT 1A receptors to flattened glucocorticoid rhythm in some part resembles their response to SSRIs.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…This is manifest in a flattening of the normal diurnal rhythm of glucocorticoid levels together with an elevation of nadir levels (Deuschle et al, 1997;Wong et al, 2000). We have recently shown in rats, that flattening the glucocorticoid rhythm, with an elevation of the nadir, causes a desensitization of somatodendritic 5-HT 1A autoreceptors (Leitch et al, 2003). Hence the response of 5-HT 1A receptors to flattened glucocorticoid rhythm in some part resembles their response to SSRIs.…”
Section: Introductionmentioning
confidence: 96%
“…Specifically we examined effects of the two treatments, alone and in combination, on the sensitivity of 5-HT 1A receptors controlling 5-HT release in the frontal cortex and on extracellular levels of 5-HT in this region. In adrenally intact male rats we used slow-release corticosterone pellets in a paradigm which we have previously shown to flatten the glucocorticoid rhythm without increasing total glucocorticoid exposure (Leitch et al, 2003). We combined this corticosterone treatment (or sham surgery) with chronic once daily injection of the SSRI fluoxetine (or vehicle).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the 5-HT 1A receptor (5-HT 1A R) is very susceptible to modulation by stress and HPA-axis activation and is well known to play an important role in the pathophysiology of mood disorders (Lopez et al, 1998;Cryan and Leonard, 2000;Leitch et al, 2003). Accumulating evidence points also to an important role for the neurotrophin brainderived neurotrophic factor (BDNF) in both the pathophysiology of mood disorders and in the therapeutic effects of antidepressants (Duman, 2002;Castren, 2004;Hashimoto et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that implantation of slowrelease corticosterone pellets in adrenally intact adult rats produces a flattened glucocorticoid rhythm, in which levels are clamped midway between the normal morning nadir and evening peak, and there is no change in overall glucocorticoid exposure (Leitch et al, 2003). Here we used this model to determine the effects of flattened glucocorticoid rhythm on hippocampal expression of mRNAs coding for three neuronal proteins using in situ hybridization histochemistry.…”
Section: Introductionmentioning
confidence: 99%